Odpowiedzi

Najlepsza Odpowiedź!
2010-01-04T18:14:38+01:00
A
3u + 2v = 2 / * (-2)
5u + 4v = 6

- 6u -4v = -4
5u + 4v = 6
-u = -2/:(-1)
u = 2

5* 2 +4v = 6
10 + 4v = 6
4v = 6 - 10
4v = - 4 /: 4
v = -1

b
3s + 5t = -6
1,5s-2t=-3 /*(-2)

3s + 5t = -6
-3s + 4t = 6
9t = 0

Równanie sprzeczne

c
5 = 3x - y
5x - 2y = 7

3x - y = 5/ *2
5x - 2y = 7 /* (-1)

6x -2y = 10
-5x + 2y = -7

x = 3

6*3 -2y = 10
-2y = 10 - 18
-2y = -8 /: (-2)
y = 4

d
x-3y=5
y+3x=-5

-3y + x = 5
y + 3x = -5 /*3

-3y + x = 5
3y +9x = -15

10x = - 10 /:10
x = -1

y + 3 * (-1) = -5
y = -5 + 3
y = -2